Analysis of Resistance Characteristics of a 37 Rod Fuel Bundle under Low Reynolds Number. (3rd December 2020) - Li, Yonghua; Li, Meijun; Guo, Yangyang
Abstract : During the working period of decay heat removal system, the flow rate of liquid sodium in wire-wrapped fuel assembly is very low, generally Re < 1000 . In the present study, both experimental methods and numerical simulation methods are applied. First, water experiment of 37-pin wire-wrapped rod bundle was carried out. Then, the numerical simulation study was carried out, the experimental data and the numerical simulation results were compared and analyzed, and a suitable turbulence model was selected to simulate the liquid sodium medium. Finally, numerical simulations under different boundary conditions were performed. Results indicate that except for the low Reynolds number k -ε turbulence model, other turbulence models have little difference with the experimental results. The results of realizable k -ε turbulence model are the most close to the experimental results. Compared with the friction factor obtained by using water medium and liquid sodium medium, the calculation results of water medium and sodium medium under the same condition are basically consistent, with the deviation within 1%. The reason is that the velocity of water is higher than sodium medium at the same Reynolds number, and the transverse disturbance caused by helical wire is larger.